The impact of interest rates on financial performance indicators of financial markets - an applied study in the Iraqi stock market for the period (2005-2013) - حيدر عباس الجنابي (Iraqi Journal for Administrative Sciences, 2025)
The financial sector has become one of the important economic sectors, which has a pivotal role in achieving progress and nourishing the rest of the sectors that make up any economy and stimulating them to grow and compete. As it overlaps with important work and relationships with other sectors. The financial markets sector represents an important part of the economies of major and developing countries alike, as it has a significant contribution to the size of the gross domestic product and has a major impact on employing workers and mobilizing other economic sectors. The financial markets sector has features that differ from other sectors, as it invests large and diversified capital. There are many contracts in terms of specifications and time factor (time periods). In view of the potential losses that may befall all sectors and entities related to the market sector, including investors, official bodies, and lenders, the process of clarifying the impact of interest rates on the stock market was an extremely important topic. The main goal of financial analysis is to provide the concerned groups with information and data about the company’s financial situation and evaluate the company’s performance during a certain period in order to assist in the company’s financial planning process, verify the extent of the company’s ability or failure to achieve goals, and obtain indicators that show whether the company’s policies are... Are they sound or need to be amended, and then help in the decision-making process within the company? Financial ratios are one of the most important and most commonly used financial analysis tools, as they express the mathematical relationship between two values or two or more items in the financial statements, and through ratio analysis The financial position of the company and its performance during a certain period can be evaluated by making comparisons between the financial ratios of a particular company and the financial ratios of similar companies. This enables the company's performance and financial position to be compared in successive periods of time and to determine its performance trends. One of the most prominent uses of financial ratio analysis is to determine the strength of the financial position of companies in the event of large fluctuations in the level of interest rates, as fluctuation in interest rates is one of the problems that many try to deal with with caution because of the danger it represents to the companies’ business, as the fluctuation in interest rates is summarized in: The benefit is that the company is unable to achieve a reasonable return on its investments and is unable to pay its obligations to creditors and fulfill its debts.